The Paris Embassy
X, 239 p.
Keywords: This collection of essays looks at Anglo-French relations from the Second World War to the advent of Margaret Thatcher's government in a new light, focusing on the work of Britain's ambassadors to France. In particular, it looks at moves towards deeper European integration, a key theme in twentieth century British foreign policy.